Changes In the Approach to Employee Training Caused by The Covid-19 Coronavirus Pandemic (Case Study) - Kornelia Polek-Duraj (Communications of International Proceedings, 2022)
The article deals with thematic issues related to training and its impact on organizations. The theoretical part presents the essence of training as well as training methods and techniques. The research part includes an empirical analysis of the training culture and the impact of the Covid-19 coronavirus pandemic on the training situation. It was assumed in the work that despite the restrictions related to the pandemic, the trainings were held, but in a slightly changed form.
Keywords: Coronavirus Covid-19; Training in the Organizations; Essence of Training